Transformation of the Constitutional Justices Tenure After the Constitutional Court’s New Act: Transformasi Masa Jabatan Hakim Konstitusi Pasca Perubahan Undang-Undang Mahkamah Konstitusi - Kurniawan, M Beni; Refiasari, Dinora (Jurnal Konstitusi, 2024)
The periodization system in the constitutional judges’ position has the opportunity to undermine the judges’ independence. the opportunity to be re-elected as an opening for political transactions between constitutional judges with the proposing institution. The enactment of Act No. 7/2020 is a new era for the system used in the constitutional judges’ term. The periodization of the Constitutional Court judges’ term was replaced based on the age limit of 70 years. This research examines the design of Constitutional Court judges’ terms after the enactment Act No. 7/ 2020. This article is written based on normative legal research. This study concludes that the transformation of the Constitutional Court judges’ term into non-periodization aims to strengthen the independence of Constitutional judges from any intervention. At the same time as a fortress from external pressure and ensures that judges do not face conflicts of interest arising from the possibility of extending the term.